EFFECT OF MIXED ROSSBY GRAVITY WAVES ASSOCIATED WITH MADDEN-JULIAN OSCILLATION ON THE CHARACTERISTICS OF TROPICAL TROPOPAUSE LAYER - Afifi, Khanifah
The tropopause inversion layer characterizes an increasing temperature gradient with a 1– 2 km thickness in the tropical tropopause layer at 14–18.5 km altitude range. This research focuses on the variation of tropopause sharpness (TS) derived using the Brunt-Vaissala frequency (N2) as a function of the temperature gradient relative to the minimum temperature. About 4,000 temperature profiles per day within 2020-2022 (3 years) from the COSMIC-2 GNSS-RO satellite were used to analyze TS. The humidity profiles at 2–20 km altitude range from COSMIC-2 were also used to investigate the distribution of integrated water vapor (IWV) values in the global equator. This research applies TS data filtering to determine the influence of the westward propagation, the Mixed-Rossby Gravity (MRG), which is associated with the intraseasonal scale of an eastward organized convective clouds propagation, the Madden-Julian Oscillation (MJO). The scope of the study area includes the Indian Ocean, the Indonesian Maritime Continents, and the Pacific Ocean throughout 10°S - 10°N and 60° - 180°E. This area is expected to have the most active convective cloud activity (low value of outgoing longwave radiation; OLR) for the MJO phases 3, 4, and 5. This research identified 21 active MJO cases using the real-time multivariate MJO index. We found, in general, the relationship between equatorial waves and TS. The mean large TS > 6.5 × 10–4s–2 corresponds to a minimum OLR value < 210 W/m2, characterizing the presence of convective clouds as a source of equatorial wave propagation. This study also shows that the TS amplitude of 16×10 –4 s–2, which propagates eastward related to MJO, is larger than the MRG signal. This study found that MRG indirectly affects TS evolution through changes in meridional winds at 100 hPa. The transition from southerly winds to northerly winds is associated with an increase of IWV up to a maximum value of 23.8 kg/m2 in the troposphere. Furthermore, it triggers the growth of MJO convective clouds. The propagation of convective clouds will increase the TS value (up to 7×10–4s–2) around 10° East Longitude from the position of the convective center.